2005
DOI: 10.1523/jneurosci.3361-04.2005
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Internal State Are Expressed in Coherent Shifts of Neuromuscular Activity inAplysiaFeeding Behavior

Abstract: The multitasking central pattern generator (CPG) that drives consummatory feeding behaviors of Aplysia can produce ingestive, egestive, and intermediate motor programs. External stimuli trigger the programs but, remarkably, do not directly specify which type of program is produced. Rather, recent work has proposed, the type of program is determined by the internal network state of the CPG that has developed in response to the previous history of the stimulation. Here we have tested a key prediction of this net… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 43 publications
3
42
0
Order By: Relevance
“…There is considerable evidence that radula movements, which are organized in an all-or-none action pattern of protraction-retraction mouth closure, constitute a highly variable component of Aplysia feeding behavior (Horn et al, 2004;Jing et al, 2004;Jing and Weiss, 2005;Lum et al, 2005;Zhurov et al, 2005;Ye et al, 2006). We now show that the temporal structure of radula bite cycles during food seeking is also a flexible constituent of this behavior.…”
Section: Operant Conditioning and Induction Of Compulsive-like Feedinmentioning
confidence: 64%
“…There is considerable evidence that radula movements, which are organized in an all-or-none action pattern of protraction-retraction mouth closure, constitute a highly variable component of Aplysia feeding behavior (Horn et al, 2004;Jing et al, 2004;Jing and Weiss, 2005;Lum et al, 2005;Zhurov et al, 2005;Ye et al, 2006). We now show that the temporal structure of radula bite cycles during food seeking is also a flexible constituent of this behavior.…”
Section: Operant Conditioning and Induction Of Compulsive-like Feedinmentioning
confidence: 64%
“…Repetitive 30-s-ISI (see Materials and Methods) stimulation of CBI-2 promotes the generation of ingestive motor programs, whereas stimulation of EN promotes the generation of egestive motor programs. Notably, in semi-intact preparations, the two CPG inputs CBI-2 and EN, respectively, elicit ingestive and egestive behaviors (Chiel et al, 1988;Jing and Weiss, 2005;Zhurov et al, 2005).…”
Section: B64 Hyperpolarization In Ingestive Versus Egestive Programsmentioning
confidence: 99%
“…If this is the case, it should be possible to experimentally change positive latencies into negative ones, and vice versa, by altering the state of the network. Previous work showed that previous history of network activity produces lasting changes in the state of the system (Proekt et al, , 2007Brezina et al, 2005;Zhurov et al, 2005). We used previously described experimental paradigms (Proekt et al, , 2007 to manipulate the state of the network and characterized the resulting changes in B64 latency.…”
Section: Dynamic Change Of B64 Latency During Program Buildup and Biamentioning
confidence: 99%
“…B65 actions suggest that inputrepresenting neurons that are themselves elements of the CPG may play a role similar to that attributed to higher-order neurons. In addition, because B65 activity may be further regulated by other inputs, the mechanisms described in here may support additional forms of network and behavior flexibility Lum et al, 2005;Proekt et al, 2005;Zhurov et al, 2005;Jing et al, 2007).…”
Section: Discussionmentioning
confidence: 87%